Russian Science and Russian State: Image of a Scientist in Modern Russian Cinema - S. M. Medvedeva (Vestnik MGIMO-Universiteta)
The article analyses the image of a scientist represented in recent Russian movies. The article discusses two groups of questions: (1) nature and role of popular science in the life of society; (2) national features of scientific cultures. The article agues that popular science should not be conceived as a week copy of the real science. On the contrary, modern models of science communication assume that popular science have its own value and is able to influence scientific practices. Simultaneously we assume, that since popular science is less integrated with international scientific norms, it can easer reveal national traditions of scientific life. As a result, the analyze of recent Russian movies shows that the tradition established in Peter I times for Russian scientists to work out their self-identity in concern with Russian state still exists (scientist- state supporter/scientist- oppositionist). Actually the modern interpretation of dilemma between state patriotism and liberalism given by modern movies shows that Russian scientist don't have real choice, because they loose anyway whereas the state always wins. So owing to recent movies this representation of hopeless destiny of a scientist is becoming widespread in Russian public culture.